Just beyond. The horror at Happy Landings - Stine, R. L. (KaBOOM!, 2020)
While Parker and Annie are on a family camping trip, they begin encountering strange creatures in the woods. First, their mom is attacked by a creepy, unidentified bird, and then the kids themselves are taken over by two alien creatures. The kids must fight to get their minds back and convince their family of what is happening before it is too late.